2017
DOI: 10.1136/bjsports-2017-097503
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of knee pain, radiographic osteoarthritis and arthroplasty in retired professional footballers compared with men in the general population: a cross-sectional study

Abstract: ObjectivesTo determine the prevalence of knee pain, radiographic knee osteoarthritis (RKOA), total knee replacement (TKR) and associated risk factors in male ex-professional footballers compared with men in the general population (comparison group).Methods1207 male ex-footballers and 4085 men in the general population in the UK were assessed by postal questionnaire. Current knee pain was defined as pain in or around the knees on most days of the previous month. Presence and severity of RKOA were assessed on st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

14
120
1
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 84 publications
(137 citation statements)
references
References 31 publications
14
120
1
2
Order By: Relevance
“…Exercise is essential for the health of the knee joint, with cartilage being able to adapt its structure, composition, and metabolism to a wide range of activities . However, very high doses of exercise such as playing sports at an elite level as well as the absence of exercise, in the forms of sedentary behavior or immobilization , are associated with cartilage loss and OA development. Therapeutic exercise is a cornerstone in the management of OA, .…”
Section: Introductionmentioning
confidence: 99%
“…Exercise is essential for the health of the knee joint, with cartilage being able to adapt its structure, composition, and metabolism to a wide range of activities . However, very high doses of exercise such as playing sports at an elite level as well as the absence of exercise, in the forms of sedentary behavior or immobilization , are associated with cartilage loss and OA development. Therapeutic exercise is a cornerstone in the management of OA, .…”
Section: Introductionmentioning
confidence: 99%
“…It is commonly assumed that sports on the elite or professional level lead to injuries, late sequelae and impairment of quality of life at an older age. To date, most studies published on this topic have focused only on one joint and or on osteoarthritis without assessing injuries during the active career [3,7,8,[12][13][14][15]26]. Some of the studies did not clearly declare the origin or characteristics of their control group [1,14,19,29] and 2 studies used military personnel [20,23] for comparison, who might be subjected to similar risk of injury as elite sportsmen.…”
Section: Discussionmentioning
confidence: 99%
“…The low prevalence of CC in Koreans, like in Chinese, might be attributable to this result. Furthermore, the type of work activity and sports involved, previous joint trauma/injury, and fractures, which may be implicated in the development of CPPD, 13,14 were not considered as compounding factors in this study. Interestingly, our study suggested an association between high levels of HbA1c and the development of CC.…”
Section: Discussionmentioning
confidence: 99%